Twitter sentiment analysis about economic recession in indonesia - Eka Putra, Fauzan Prasetyo; Maulana, Fairuz Iqbal; Akbar , Nawawi Muhammad; Febriantoro, Wicaksono (Association for Scientific Computing Electrical and Engineering, 2023)
As one of the most popular social media platforms, Twitter enables users to express their opinions on diverse concepts, products, and services. Large quantities of data shared as tweets can be mined for user feedback and used to improve the quality of products and services. Using Twitter data and social media sentiment analysis, tracking how people feel about the recession in real time is possible. As a consequence, relevant organizations or governments can take preventative measures against the disinformation and unlawful conduct caused by the effects of the recession. This study aims to determine if there is a correlation between how people on Twitter feel about the recession. This study's data acquisition utilized